2013
DOI: 10.1007/s00737-013-0357-8
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of maternal attachment and infant developmental outcomes

Abstract: Extant research has demonstrated that compared to adults with insecure attachment styles, more securely attached parents tend to be more responsive, sensitive, and involved parents resulting in improved outcomes for their children. Less studied is the influence of a mother's attachment style on her attachment to her unborn child during pregnancy and the consequent developmental outcomes of the child during early childhood. Thus, the aim of this prospective longitudinal study was to examine the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
144
0
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(167 citation statements)
references
References 51 publications
10
144
0
13
Order By: Relevance
“…The significance of this lies in understanding the role of internal working models in perpetuating poorer outcomes, even across generations (Alhusen, Hayat, & Gross, 2013;Burke, 2003) and gives meaning to intervention studies identifying the positive impact of mindfulness on mental health and relationships (Barnes, Brown, Krusemark, Campbell, & Rogge, 2007;Brown, et al, 2007;Carson, Carson, Gil, & Baucom, 2007;Shaver, Lavy, Saron, & Mikulincer, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this lies in understanding the role of internal working models in perpetuating poorer outcomes, even across generations (Alhusen, Hayat, & Gross, 2013;Burke, 2003) and gives meaning to intervention studies identifying the positive impact of mindfulness on mental health and relationships (Barnes, Brown, Krusemark, Campbell, & Rogge, 2007;Brown, et al, 2007;Carson, Carson, Gil, & Baucom, 2007;Shaver, Lavy, Saron, & Mikulincer, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…La literatura indica que gran parte de la capacidad para desarrollar una identidad materna positiva radica en el propio estilo de apego infantil de la madre, desde el cual se han construido las relaciones con otros y la capacidad de percibirse a sí misma como proveedora de protección y cuidados; ambas cuestiones fundamentales en el establecimiento del vínculo materno-fetal (Shieh y Kravitz, 2006). Los datos demuestran también que mujeres con estilos de apego inseguros que dificultan su vinculación con el feto, no tienden a beneficiarse de intervenciones destinadas a fortalecer la filiación afectiva con sus hijos, ya que la confianza en el otro y la alianza terapéutica pueden estar comprometidas (Alhusen et al, 2013). Conocer la historia vincular de la madre permite re-elaborarla y fortalecer las relaciones afectivas presentes con la pareja, grupo de amigos y familia, siendo estas indispensables para la percepción positiva de apoyo y seguridad durante el embarazo, actuando como fuente de salud.…”
Section: Propuesta De Intervención Tempranaunclassified
“…Una experiencia similar es llevada a cabo por medio del programa Minding the Baby, cuyo principal objetivo es el fortalecimiento del vínculo madre-bebé comenzando en el embarazo. Esta intervención dirigida igualmente a población de riesgo y vulnerabilidad psicosocial (madres adolescentes con historia de trauma) trabaja desde un enfoque interdisciplinar (enfermera y trabajador social), por medio de la psicoterapia basada en la mentalización buscando una mejoría en la capacidad reflexiva de las madres (Alhusen et al, 2013;Slade et al, 2005). Finalmente, cabe afirmar que una intervención interdisciplinar basada en el vínculo materno-fetal ofrecería efectos positivos a corto y largo plazo de los que las familias pudieran beneficiarse.…”
Section: Propuesta De Intervención Tempranaunclassified
“…Moreover, the fetus will achieve better growth than others. In this study, mothers with higher levels of prenatal attachment turned out to be more responsible, sensitive and committed than mothers with less fetal attachment [7]. Maternal attachment may lead to increased IQ in infants, and they are more engaged with objects at 9 months of age [8].…”
Section: Introductionmentioning
confidence: 63%
“…They found that lack of maternal-fetal attachment (b = 0.97 95% CI [0.97-0.98]; p < 0.001) and postpartum depression (b = 0.97 CI [0.96-0.99]; p < 0.001) are two important predictors for the early development of children in the initial years of growth. During pregnancy, women with lower fetus--attachment, and those with postpartum depression had more developmental delay compared to those with more attachment [7]. Alhusen et al believes in the impact of maternal-fetal attachment and postpartum depression on the infants' motor development.…”
Section: Discussionmentioning
confidence: 99%